Implementasi Moderasi Beragama melalui Pembelajaran Pendidikan Agama di SMP Negeri 3 Mengkendek Kabupaten Tana Toraja - Abdul Asis; A. Riawarda; Rukman Abdul Rahman Said (Institut Agama Islam Negeri Palopo, 2023)
The purpose of this research is to analyze the implementation of religious moderation in SMP Negeri 3 Mengkendek, Tana Toraja Regency. This type of qualitative research with a pedagogic approach. Primary data sources come from interviews, while secondary data are taken from documents related to research. The results of the study show that the implementation of religious moderation in SMP Negeri 3 Mengkendek Tana Toraja Regency has indirectly been formed, this is evidenced by the absence of coercion (respect for individual rights) in religion and tolerance built by all groups starting from family, school , and society. Teachers on the subject matter of Islamic Religious Education (PAI) at State Junior High School 3 Mengkendek provide reinforcement of religious education in the learning process, namely through providing information and sources related to morals, as well as providing lesson assignments that aim to train students' responsibilities . In addition, strengthening the implementation of religious moderation in Islamic education learning at SMP Negeri 3 Mengkendek, namely the existence of local community wisdom that is so strong that it has an impact on the curriculum in educational institutions in Kab. Toraja